2022
DOI: 10.3389/fgene.2022.905508
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fatty Acid Metabolism in Lung Adenocarcinoma

Abstract: Background: Lung adenocarcinoma (LUAD) is the most common subtype of non-small cell lung cancer. Fatty acid metabolism takes part in malignancy progression. However, the roles fatty acid metabolism plays in LUAD are still unclear.Methods: The transcriptomic and clinical data of LUAD patients from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases were extracted. ssGSEA, WGCNA, univariable Cox regression, and LASSO Cox regression analyses were performed to identify the fatty acid metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…LUAD tissues had a lower score of the FAM-related pathway compared to para-cancer tissues. This also indicated that abnormal FAM was involved in the progression and prognosis of LUAD, which is consistent with the characterization results of FAM in LUAD by Wang et al (2022a ). As a new treatment method, immunotherapy has become an effective strategy to treat cancers ( Riley et al, 2019 ).…”
Section: Discussionsupporting
confidence: 88%
“…LUAD tissues had a lower score of the FAM-related pathway compared to para-cancer tissues. This also indicated that abnormal FAM was involved in the progression and prognosis of LUAD, which is consistent with the characterization results of FAM in LUAD by Wang et al (2022a ). As a new treatment method, immunotherapy has become an effective strategy to treat cancers ( Riley et al, 2019 ).…”
Section: Discussionsupporting
confidence: 88%
“…The present study aimed to determine whether LODDS could be utilized to predict the cancer-specific survival (CSS) or overall survival (OS) of patients with node-positive (N1/N2 classification) LNET using the Surveillance, Epidemiology, and End Results (SEER) database. Based on LODDS, the research intended to construct two visualized and online nomograms which are practical tools for clinical prediction used in many diseases (28)(29)(30)(31)(32). To facilitate clinical use, we also constructed two visualized and online nomograms for LNETs.…”
Section: Introductionmentioning
confidence: 99%
“…To improve prognosis assessment and individualized treatment, it is essential to research potential biological pathways and find reliable prognostic biomarkers. Researchers are beginning to comprehend the significance of FAM in relation to tumorigenesis, development, drug resistance, and prognosis in LUAD as a consequence of rigorous studies on metabolic reprogramming ( 39 , 40 ). We have a limited understanding of the connection between lncRNA and FAM in LUAD.…”
Section: Discussionmentioning
confidence: 99%